2015
DOI: 10.1111/jan.12759
|View full text |Cite
|
Sign up to set email alerts
|

Physician substitution by mid‐level providers in primary healthcare for older people and long‐term care facilities: protocol for a systematic literature review

Abstract: This review will contribute to the knowledge on effects of physician substitution in healthcare for older people and factors that influence the outcomes. This knowledge will guide professionals and policy administrators in their decisions to optimize healthcare for older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…For background and an extensive method section, we refer readers to the study protocol (Lovink et al . ) and the PROSPERO database of the Centre for Reviews and Dissemination, CRD42015024586. This review is not a registered Cochrane review as we wished to provide a broad insight into the current state of evidence on this topic by including not only randomized controlled trials (RCTs) but also other comparative studies as well.…”
Section: The Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…For background and an extensive method section, we refer readers to the study protocol (Lovink et al . ) and the PROSPERO database of the Centre for Reviews and Dissemination, CRD42015024586. This review is not a registered Cochrane review as we wished to provide a broad insight into the current state of evidence on this topic by including not only randomized controlled trials (RCTs) but also other comparative studies as well.…”
Section: The Reviewmentioning
confidence: 99%
“…This study is a systematic literature review reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement (Moher et al 2009) as described in the Cochrane Handbook (Higgins & Green 2011). For background and an extensive method section, we refer readers to the study protocol (Lovink et al 2015) and the PROSPERO database of the Centre for Reviews and Dissemination, CRD42015024586. This review is not a registered Cochrane review as we wished to provide a broad insight into the current state of evidence on this topic by including not only randomized controlled trials (RCTs) but also other comparative studies as well.…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review showed that substituting nursing home physicians with NPs, PAs or RNs appears to achieve at least as good resident and process of care outcomes as care provided by physicians 14. In a focus group study with professionals in Dutch nursing homes, the contributions of NPs, PAs and RNs to quality healthcare, provision of resident-centred care and strengthening of the care team was considered an added value 15.…”
Section: Introductionmentioning
confidence: 99%